KEPEDULIAN MAHASISWA TERHADAP KEBERSIHAN DI LINGKUNGAN FAKULTAS ILMU SOSIAL UNIVERSITAS NEGERI PADANG - M. Rizki Saputra; Ernawati Ernawati (JURNAL BUANA, 2023)
The purpose of this study is to know the correlation of environmental knowledge to caring attitudes, know the correlation of social interaction to caring attitudes, and know the correlation of environmental knowledge and social interaction to caring attitudes. This research location takes place at the Faculty of Social Sciences, Padang State University. The population of this study is all students visitors to Selasar Faculty of Social Sciences Universitas Negeri Padang. Samples in accidental sampling. The results showed that environmental knowledge had no correlation to caring attitudes, this was evidenced by significant values of 0.494 > 0.05 and Fhitung (0.884) < Ftabel (3.14). The variable of social interaction there is a correlation to caring attitudes, this is evidenced by the significant value of 0.001 < 0.05 or Fhitung 12,239 > Ftabel 3.14 and simultaneously from both independent variables there is a significant correlation to caring attitudes, this is evidenced from Fhitung (6,308) > Ftabel (3.14) with a significant value of 0.003 < 0.05 then H0 rejected and Ha accepted.